Urgensi Adaptasi Teknologi bagi Masyarakat Profesi di Era Society 5.0 - Raka Ramandita; Anwar Sanusi; Wulandari Wulandari; Andri Azis Putra; Fuad Nawawi (UIN Sunan Gunung Djati Bandung, 2023)
This research aims to discuss the urgency of technological adaptation in the era of society 5.0. This research uses a qualitative approach by applying descriptive-analytical methods. The results and discussion in this study show that for people who are not yet technologically literate, they should be literate as soon as possible to adapt, mingle, and cooperate with technology in this day and age. Because if it is not done as soon as possible, it will cause further backwardness in following the development of this era, which is one of the causes of someone's difficulties in living life. Whereas literally, technology itself was created to facilitate human life. Broadly speaking, this research concludes that there are many digital media platforms such as; Facebook Market Place, Instagram Shop, Tik Tok Shop, Shopee, Tokopedia, Lazada, Fiverr, Open Sea, Gojek, and also Grab that can widely market products and services today. Therefore, this study recommends that professional societies who are not yet technologically literate should be technologically literate as soon as possible to adapt to the times, and make innovations and solutions in developing and marketing through digital media that are being widely used in the era of society 5.0.